2023
DOI: 10.58763/rc202342
|View full text |Cite
|
Sign up to set email alerts
|

Closure of companies in the tourism sector in the municipality of Leticia: a characterization of the factors involved

Darwin Irne Ney González Ávila,
Diana Paola Garzón Salazar,
Verenice Sánchez Castillo

Abstract: Tourism is the predominant economic activity in the municipality of Leticia (Amazonas) since the natural potential of the territory has allowed it to consolidate itself as an international attraction. However, contradictorily, companies engaged in this activity have high closure rates. The objective of the investigative exercise was to characterize the factors that led to the closure of companies in the tourism sector in the municipality of Leticia. The study sought to know the leading causes of this phenomeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This has led them to consider themselves as sources of inspiration and motivation to maintain the perspective of their projects in the long term, being as such entrepreneurs for the development of society (González Ávila et al, 2023;Guatemala Mariano & Martínez Prats, 2023). As other studies focused on the life project have shown, these positions encourage positive results and promote personal growth, and resilience to negative or disruptive factors (Monzón Pinglo et al, 2023;Rosario Quiroz & Espinoza Oncoy, 2023), facilitating a better response to them and, ultimately, represent an important identity element (Promise Ogolodom et al, 2023).…”
Section: Research Articlementioning
confidence: 99%
“…This has led them to consider themselves as sources of inspiration and motivation to maintain the perspective of their projects in the long term, being as such entrepreneurs for the development of society (González Ávila et al, 2023;Guatemala Mariano & Martínez Prats, 2023). As other studies focused on the life project have shown, these positions encourage positive results and promote personal growth, and resilience to negative or disruptive factors (Monzón Pinglo et al, 2023;Rosario Quiroz & Espinoza Oncoy, 2023), facilitating a better response to them and, ultimately, represent an important identity element (Promise Ogolodom et al, 2023).…”
Section: Research Articlementioning
confidence: 99%